2021
DOI: 10.1016/j.jmig.2020.08.486
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Wait Time to Hysterectomy for Benign Gynecologic Disease

Abstract: To determine the impact of surgical wait time on healthcare use and surgical outcomes for patients undergoing hysterectomy for benign gynecologic indications. Design: Retrospective cohort study. Setting: Urban, academic tertiary care center. Patients: Patients who underwent hysterectomy for benign disease between 2012 and 2018. Interventions: None. Measurements and Main Results: Patients were categorized into 2 groups, dichotomized by surgical wait times >30 days or ≤30 days. Healthcare use was measured by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…(20, 21) Delaying surgeries considered less urgent, is associated with an increase cost to patients (e.g., increased pain, decreased quality of life) and the healthcare system. (22-26) Our study confirmed that perceived physical health was compromised due to the delays in surgery; however, the physical impact was less prominent and perhaps the driver of more significant effects on participants’ mental health and quality of life.…”
Section: Resultssupporting
confidence: 61%
“…(20, 21) Delaying surgeries considered less urgent, is associated with an increase cost to patients (e.g., increased pain, decreased quality of life) and the healthcare system. (22-26) Our study confirmed that perceived physical health was compromised due to the delays in surgery; however, the physical impact was less prominent and perhaps the driver of more significant effects on participants’ mental health and quality of life.…”
Section: Resultssupporting
confidence: 61%
“…21,22 Delaying surgeries considered less urgent is associated with an increased cost to patients (e.g., increased pain, decreased quality of life) and the health care system. [23][24][25][26][27] Our study confirmed that perceived physical health was compromised by the delays in surgery; however, the physical impact was less prominent and perhaps the driver of more significant effects on participants' mental health and quality of life.…”
Section: Discussionsupporting
confidence: 59%
“…Establishment of maximum waiting time targets is a promising strategy to avoid morbidities and surgical complications. In a retrospective cohort study conducted by Traylor et al among 277 patients who underwent hysterectomy for benign gynecologic disease from 2012 to 2018, patients with a surgical waitlist time of more than 30 days were 3.22 times more likely to be readmitted [ 7 ]. Likewise, they were shown to have an increased frequency of healthcare use and decreased quality of life.…”
Section: Discussionmentioning
confidence: 99%